Odrednice i operacionalizacija modela izobrazbe pilota Hrvatskoga ratnog zrakoplovstva - Grozdanić, Berislav (Promet - Traffic&Transportation, 2012)
The models for training of student-pilots for the needs of the Croatian Air Force have been created by accommodation of the models applied by the air forces of western nations (Germany, United Kingdom, Israel and America) and further conditioned by the requirements, financial potential and finally-the aspired-to qualities of graduated aeronautical engineers -future pilots. . . For the first time in the Republic of Croatia the education and training of full-time student-pzlots have been organized in the civilian educational system with the University of Zagreb (Faculty of Traffic Engineering) using the course and program of instruction granting the highest level of education - a university degree. Highest quality education/training is provided y top specialists in the field, university teachers employed with the Faculty of Traffic Engineering and teaching members of the Croatian Air Forces (flight instructors). In this manner we have succeeded in providing a highly graded education and training of future pilots of the Croatian Air Force in the country.